Potential of Qust Al Hindi (Saussurea lappa) Root as Anti-hyperuricemia: Literature Review - Marwah, Marwah; Sukmawati, Sukmawati; Muflihunna, A. (Pharmaceutical Reports, 2024)
Hyperuricemia is a condition characterized by increased levels of uric acid due to dysfunction in production or excretion. Uric acid is the product of purine catabolism originating from the degradation of purine nucleotides that occur in all cells. The first-line treatment for hyperuricemia is allopurinol. have side effects so that the use of traditional medicine with natural ingredients can be used as an alternative treatment. Therefore, it is necessary to develop compounds with xanthine oxidase inhibitor activity derived from natural plants with lower side effects. Xanthine oxidase is an enzyme that plays a role in catalyzing the oxidation of hypoxanthine to xanthine and uric acid. Qust al hindi contains several chemical compounds including flavonoids, steroids, terpenes, alkaloids, sesquiterpenes, costunolide, dehydrocostus lactone, cynaropicrin, and chlorogenic acid. This review will discuss the qust al hindi plant which has the potential to be an antihyperuricemia drug using the library study method. Data search was carried out using online search engine instruments such as Google, PubMed and Science Direct.